Functionalization of an Antisense Small RNA. Issue 5 (27th February 2016) - Rodrigo, Guillermo; Prakash, Satya; Cordero, Teresa; Kushwaha, Manish; Jaramillo, Alfonso
Abstract: In order to explore the possibility of adding new functions to preexisting genes, we considered a framework of riboregulation. We created a new riboregulator consisting of the reverse complement of a known riboregulator. Using computational design, we engineered a cis -repressing 5′ untranslated region that can be activated by this new riboregulator. As a result, both RNAs can orthogonally trans -activate translation of their cognate, independent targets. The two riboregulators can also repress each other by antisense interaction, although not symmetrically. Our work highlights that antisense small RNAs can work as regulatory agents beyond the antisense paradigm and that, hence, they could be interfaced with other circuits used in synthetic biology. Graphical abstract: Highlights: We have engineered a riboregulator as the negative-sense strand of another riboregulator. This new RNA molecule performs the cellular function of titration of a functional molecule or trans -activation of gene expression. We have followed a computational design approach with energetic and structural criteria to obtain the nucleotide sequence of a 5′ untranslated region responding to the new riboregulator. We have engineered different regulatory circuits with trans -activating and anti- trans -activating small RNAs and characterized them at the population and single-cell levels.